2013
DOI: 10.1111/bph.12135
|View full text |Cite
|
Sign up to set email alerts
|

8‐BuSATP derivatives as specific NTPDase1 inhibitors

Abstract: Background and Purpose Ectonucleotidases control extracellular nucleotide levels and consequently, their (patho)physiological responses. Among these enzymes, nucleoside triphosphate diphosphohydrolase‐1 (NTPDase1), −2, −3 and −8 are the major ectonucleotidases responsible for nucleotide hydrolysis at the cell surface under physiological conditions, and NTPDase1 is predominantly located at the surface of vascular endothelial cells and leukocytes. Efficacious inhibitors of NTPDase1 are required to modulate respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…We previously observed that ticlopidine inhibited recombinant human NTPDase1 [46]. In this work we verified if this compound can be used as a specific inhibitor of the enzyme.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…We previously observed that ticlopidine inhibited recombinant human NTPDase1 [46]. In this work we verified if this compound can be used as a specific inhibitor of the enzyme.…”
Section: Resultssupporting
confidence: 57%
“…Sections of 6  μ m were obtained and fixed in 10% phosphate-buffered formalin mixed with cold acetone as before [46]. Localization of ectonucleotidase activities was determined using the Wachstein/Meisel lead phosphate method [47].…”
Section: Methodsmentioning
confidence: 99%
“…However, these tool compounds have many shortcomings 108 . ARL 67176 and 8-butylthio-ATP are nucleotide analogues with marginal selectivity and potency, and although they have been used for in vivo experiments, the pharmacokinetic behaviour of these compounds is unknown 109,110 . Polyoxotungstate (POM-1), which is a high-molecular-mass metal complex, raises similar concerns.…”
Section: B Cellsmentioning
confidence: 99%
“…36,37 Briey, COS-7 cells (in 15 cm dishes) were transfected with an expression vector (pcDNA3) incorporating the cDNA that encodes each ectonucleotidase using Lipofectamine (Invitrogen) and harvested 40-72 h later. Cell membranes were prepared as described elsewhere.…”
Section: Transfection and Membrane Preparations Of Human Ntpdasesmentioning
confidence: 99%